INNOVATION OF ISLAMIC RELIGIOUS EDUCATION TEACHERS' LEARNING IN INSTRUCTIVE VALUES OF RELIGIOUS MODERATION AT SMP MUHAMMADIYAH 07 MEDAN - Hafiza Husna; Selamat Pohan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The purpose of this study was to explore the learning innovations implemented by Islamic Religious Education (PAI) teachers in instilling the values ​​of religious moderation at SMP Muhammadiyah 07 Medan. This study used a descriptive qualitative approach, this study collected data through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that PAI teachers implemented various learning innovations, such as the use of digital technology, interactive discussions, and experience-based approaches to improve students' understanding of religious moderation. This strategy is effective in forming inclusive and tolerant attitudes in students, even though there are obstacles such as the diversity of student backgrounds and the influence of the social environment.